STUDY ON SULFIDE GOLD ORE BIOOXIDATION USING COLUMN BIOOXIDATION METHOD AT PT J RESOURCES BOLAANG MONGONDOW - Bernadeta Sipayung, Angelia
Sulfide gold ore is categorized as refractory or difficult-to-treat ore due to the difficulty in direct cyanidation process because of the low gold recovery. Refractory gold ore requires pretreatment prior to cyanidation to increase the gold extraction. An alternative way, biooxidation, is considered because it is more environmentally friendly and has lower operational costs compared to other methods such as roasting or pressurized oxidation. To investigate the biooxidation efficiency, a pilot scale of column biooxidation was carried out using iron-and sulfur-oxidizing bacteria at PT J Resources Bolaang Mongondow. Sulfide gold ore from PT J Resources Bolaang Mongondow was used in this study. The experiment sequence started with ore preparation process including ore crushing, sieving to obtain two ore size fractions of -12+6 mm and -25+12 mm; followed by homogenization and sampling for the purpose of ore characterization and biooxidation experiments. In parallel, the bacterial growth curve was constructed to determine the optimum time for bacterial incubation. In the next step, a preliminary biooxidation experiment was carried out using 3 bacterial species, followed by cyanidation experiment which aimed to select two bacterial species for the subsequent core biooxidation experiments. Direct cyanidation experiment was also performed in order to determine the effect of biooxidation process. Furthermore, the core biooxidation experiments with the following cyanidation were conducted with variations on biooxidation medium, bacterial culture, and ore size fraction to the extent of determining the best condition for biooxidation process. Finally, XRD and FTIR were conducted on the residue at the optimum biooxidation condition. The results revealed that the biooxidation using Citrobacter freundii SKC-4 and Alicyclobacillus ferrooxydans achieved the highest gold extraction. The gold extraction without and with biooxidation were 21.78% and 28.99%, respectively. This low extraction level confirmed the refractory properties of the ore. Biooxidation pretreatment has positively affected to increase the gold extraction level at the optimum condition: utilization of modified SKC-Broth medium, mixed culture of Citrobacter freundii SKC-4 and Alicyclobacillus ferrooxydans and on ore size of -12+6 mm. The highest cyanide consumption was obtained by direct cyanidation experiment. Through biooxidation process, the cyanide consumption has successfully reduced from 0.252 kg/ton to 0.202 kg/ton.